(untitled) (REMUNOM, 2025)
The article discusses the correlation between performance evaluation and organizational climate. Additionally, it provides an analysis of how these factors interact with individual and collective performance within organizations. All of this is done through bibliographic analysis, where the implementation of modern tools such as the Balanced Scorecard and People Analytics was investigated.